Creación de una tienda virtual de tarjetas personalizadas para la ciudad de Guayaquil - Cevallos Carabajo, Tatiana Elizabeth (2011)
The present project is based on the creation of a virtual customized card store of gifts for the city of Guayaquil, where the people can express their feelings through customized cards, where she is begun with a brief investigation of market, in which this was demonstrated that virtual card stores do not exist of customized gifts, would be an advantage because the client in a matter of seconds can express his feelings. We will make the chain of value by means of statistical data, investigations and surveys, which helped to the determination of the factors and immersed variables us in the execution of an activity of this type, stop of this form to take passage to the structuring of the same in the development of a cash flow. Later, by means of the use of the financial tools, the TIR, the Payback and finally a sensitivity analysis through Ball Crystal with these tools takes step to the estimation of the viability of the project of investment and to the yield that is going away to obtain with the implementation of the virtual card store of gifts. The present subject is presented in four parts. In first details the aspects of the product, second are: a organizational study, investigation of market, strategic analysis and technical study, in the third section appears the financial study. Finally, the conclusions and recommendations obtained on the basis of the results of the studies previously described appear.